Musculoskeletal Metastasis From Soft-tissue Sarcomas: A Review of the Literature. Issue 11 (1st June 2022) - Pretell-Mazzini, Juan; Seldon, Crystal S.; D'Amato, Gina; Subhawong, Ty K.
Abstract : Soft-tissue sarcomas are a rare and extremely heterogeneous group of cancers, representing <1% of all human malignancies. The lungs are the most common site of distant metastasis, followed by the bone, lymph nodes, liver, brain, and subcutaneous tissue. Clinical experience suggests that skeletal metastasis is part of the natural history affecting the prognosis and quality of life in these patients. Approximately 2.2% of patients have skeletal metastasis at diagnosis. However, up to 10% will develop skeletal metastasis after a mean interval of 21.3 months. Although systemic therapy with conventional chemotherapy remains the primary treatment modality for those with metastatic sarcoma, increased survival has been achieved in selected patients who receive multimodality therapy, including surgery, for their metastatic disease. The 5-year overall survival of patients with isolated bone metastases was 41.2% (26.9% to 54.9%), which decreased to 32.9% (21.2% to 45.1%) in the setting of combined bone and lung metastases. Moreover, the resection of the primary soft-tissue sarcoma is a predictor of survival, resulting in a 58% decrease in mortality after surgery (hazard ratio, 0.42, P = 0.013). Understanding the effect of these metastases on patient survival may influence imaging, surveillance, and treatment decisions.